ANALISIS SEMIOTIK DALAM LAGU BANDA NEIRA YANG BERJUDUL “YANG PATAH TUMBUH, YANG HILANG BERGANTI” - Hamzah silahul Islam Al-an'shory (IKIP Siliwangi, 2022)
This research is based on the many songs that are difficult to understand its meaning. A song is a series of tones combined with harmonious rhythms and complemented by poems that form a beautiful harmonisation. The song conveys its messages through lyrics that tell about a journey or or a picture of one's life therefore the song is often used as a medium to express feelings towards others. The purpose of this study was to analyze the meaning of Banda Neira's song